Modeling Work Practices Under Socio-Technical Systems For Sustainable Manufacturing Performance - Qureshi, Muhammad Imran; Rasiah, Rajah; Al-Ghazali, Basheer Mohammed; Haider, Maqsood; Jambari, Hanifah; Iswan, Iswan; Sasmoko, Sasmoko (MDPI AG, 2019)
In light of the overwhelming consumption of resources by the manufacturing sector, this paper examined three key subsystems that are critical in greening the sector. Whereas the extant literature has focused on technological development to reduce environmental damage, it has not analyzed profoundly how manufacturing processes can be greened effectively. Hence, using carefully gathered data of 299 respondents and structural equation modeling, this paper sought to investigate the mediating effect of social, environmental, and technical subsystems on the relationship between management support and sustainable manufacturing performance. The results show that management support has a positive relationship with sustainable manufacturing performance (p < 0.005), while social, environmental, and technical subsystems partially mediate this relationship. Hence, efforts must be taken to encourage management of manufacturing firms to support sustainable management performance, while at the same time supporting them to introduce innovative social, environmental, and technical practices.